UPMARKET STRATEGY FOR THE PROFESSIONAL DEVELOPMENT OF ENGINEERS WITH HEARING IMPAIRMENTS - Avdeeva, Anna; Emelyanov , Vasily; Novikov, Pavel (Revista Inclusiones, 2020)
The paper is devoted to the recent issue of the professional development of people with hearing impairments. In the context of topical problems of inclusive higher education, the problem of studying professional development assumes a special scientific and practical prominence. The upmarket strategy is presented as a dynamic system of personal professional orientation, directed at a conscious change and designing of life in the context of its professionalism and forming a professional future. This research studies presented personal and environmental factors of the upmarket strategy for the professional development of engineers with hearing impairments. Based on the qualitative research method such as biographical interview, the scientific work revealed the characteristics of upmarket strategies for the professional development of engineers with hearing impairments. The paper identifies and discusses the main personal factors affecting the process of forming the competence of upmarket specialists with hearing impairments and the multi-functionality of their professional activities. It is due to the formation of operational and tactical psychological characteristics that an upmarket scenario of personal and professional development is materializing for engineers with hearing impairments.